PENGAWETAN SUSU KEDELAI DENGAN PENAMBAHAN NIPAGIN SELAMA PENYIMPANAN - Budi Suarti; Taufik .; Agung Saputra (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This study aims to determine the effect of total nipagin and storage time on the quality of soybean milk. This research uses complete Randomized Design (CRD) factorial with (2) two replication. Factor I is the total Nipagin with password (N) which consists of 4 standard, namely: N0 = 0%, N1 = 0.03%, N2 = 0.06% and N3 = 0.09%. Factor II is a password storage L (L), which consists of 4 standard, namely: L0 = 0 days, L1 = 5, L2 = 10 days and L3 = 15 days. Parameters analyzed were: pH, Protein, Fat, Organoleptic: aroma, and taste.Statistical analysis results on each parameter gives the following conclusion: the highest pH in treatment L1 6,165 and 4,346 low pH in treatment L3. 1,810% high protein in treatment N3 and 1,606% lowest protein found in treatment N0. 1,823% high protein in treatment L0 and 1,601% Protein lowest in treatment L3. 2,335% high fat in treatment N3 and low fat 2,227% in treatment N0. Highest fat 2,488% in treatment with the lowest fat L0 and 2,050% in treatment L3. Aroma highest in treatment N3 3,296 and 2,375 aroma lowest in treatment N0. Aroma highest in treatment L0 3,008 and 2,650 aroma lowest in treatment L3. Taste highest in treatment N3 3,525 and 3,062 low taste in treatment N0. Taste highest in treatment L0 3,800 and 2,762 low taste in treatment L3.